(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article covers the fact that in the era of globalization, the development of science is associated with the development of Natural Sciences, the methodology for teaching Natural Sciences on the basis of STEAM education is widely covered. In order to train competitive personnel, improve the quality of Education, introduce advanced educational technologies into the industry, train highly qualified specialists with the skills of applying modern knowledge and pedagogical-innovative technologies, the analysis of the method and structure of the principle of "Heard-saw-done" of the STEAM educational innovation cluster based on Natural Sciences is carried out.